Thermodynamic analysis of a single cylinder crank-rocker engine - Mohammed, S.E. (Asian Research Publishing Network, 2016)
A thermodynamic model for the simulation of a single curved-cylinder crank-rocker engine which operates on gasoline fuel is presented. The thermodynamic model is based on the single and two-zone heat release models. The general model was expanded to include friction losses as a function of engine speed and combustion efficiencies at different operating points. The model was developed in MATLAB to predict engine performance and efficiencies on a motorcycle engine. The calculated data is then used to plot various thermodynamic parameters and the engine performances with respect to crank angle. The engines volume, indicated cylinder pressure, heat release rate, pressure-volume diagram, and engine brake torque have been evaluated at different crank angle positions. The results from the simulation model were plotted and compared with existing data. It was found that for the same engine capacity, the performance of the crank-rocker engine was better than the slider-crank engine when both utilized the same injection timing. Â©2006-2016 Asian Research Publishing Network (ARPN).